T-norms and t-conorms on a family of lattices - Bejines-López, Carlos (Elsevier, 2021)
This paper provides a complete classification of all t-norms on a family of lattices in terms of t-norms on discrete chains. Moreover, the cardinal of some classes on discrete chains is computed. Therefore, the number of t-norms on the family of lattices is obtained. Also, new results involving Archimedean and divisible t-norms are presented. Finally, we bring out dual results for t-conorms.
Keywords: Matemáticas difusas; T-norms